Perubahan Perilaku Anak-Anak Panti Asuhan yang Tercermin Dalam Drama Ashita, Mama ga Inai Karya Saya Matsuda - Palupy, Tia Eka Retno; Rauh Artana, I Nyoman; Ari Sulatri, Ni Luh Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 2 (2021), 2021)
The research was titled "The Behavior of Orphanage Children in the Drama Ashita, Mama ga Inai by Saya Matsuda". Research aims to know the living environment of the orphanage children, behavior of orphanage children at the time of trial before and after the trial with the adoptive parents. The study used literary psychology theory from Endaswara and the theory of behaviorism of B. F Skinner. The method used in this research is a descriptive qualitative. The results of the analyzing show orphanage children’s simply life. being the countryside and the orphanage living the life with responsibility. The orphanage children’s behavior are describes as having undergone trials with new adoptive parents, a changes due to the uncomfortable feeling of affection given by adoptive parents. The cause of the inconvenience is because the children had previously suffered trauma after being abandoned by their biological parents.